Architectures of Emergency in Turkey (London)
xiv, 225 sayfa
Keywords: “Challenging existing political analyses of the state of emergency in Turkey, this volume argues that such states are not merely predetermined by policy and legislation but are produced, regulated, distributed and contested through the built environment in both embodied and symbolic ways. Contributors use empirical critical-spatial research carried out in Turkey over the past decade, exploring heritage, displacement and catastrophes. Contributing to the broader literature on the related concepts of exception, risk, crisis and uncertainty, the book discusses the ways in which these phenomena shape and are shaped by the built environment, and provides context-specific empirical substance to it by focusing on contemporary Turkey. In so doing, it offers nuanced insight into the debate around emergency as well as into recent urban-architectural affairs in Turkey“ --